Spatio-temporal heterogeneity of metro ridership under major epidemic conditions - Baixi Shi; Lijie Yu; Qi Yang; Na Zhang; Nanxi Yang (PLoS ONE, 2025)
The COVID-19 epidemic has significantly altered travelers' behavior, therefore influenced how land use impacts subway ridership. This paper investigates these changes by employing a Geographically and Temporally Weighted Regression (GTWR) model to analyze the spatial and temporal impacts throughout the pandemic. The findings reveal that the outbreak notably reduced metro trip generation across all land use types except residential. Post-pandemic, the influence of workplace, park and green space, and educational land uses in the city center increased. Additionally, workplace land use in rapidly developing areas emerged as a critical factor in boosting metro travel post-epidemic. These insights suggest that commuting, school travel, and outdoor recreation are primary drivers of subway ridership recovery. These results can assist local governments and metro managers in optimizing land use planning and development strategies in the future.